Research on Batteries Equalization Method for Power Grid Energy Storage. Issue 1 (1st January 2022) - Zhao, Guangjin; Hu, Yuxia; Dong, Ruifeng; Zhao, Dawei; Lyu, Nawei; Zhang, Wenfei
Abstract: In recent years, with the continuous promulgation of relevant national energy storage strategies and policies and the rapid development of electrochemical energy storage technology, energy storage systems are being used more and more widely in power grids. Lithium-ion batteries have become the main battery for energy storage system applications by virtue of their high energy density, high cycle times, low self-discharge rate and low environmental pollution. In grid energy storage applications, it is often necessary to connect a large number of batteries in series and parallel to meet capacity and voltage requirements, which can lead to the amplification of very small differences in parameters between individual batteries and accumulate during charging and discharging work, eventually causing a decrease in the energy efficiency of the battery pack, a decrease in service life, and even explosive accidents. The equalization technology can well improve the imbalance problem caused by the inconsistent performance parameters between single cells, and has become a hot spot for research in recent years. In this paper, based on the analysis of battery characteristics and the characteristics of energy storage applications, we design an equalization current algorithm for battery pack under charging and discharging conditions, and design a bi-directional equalization circuit for single battery equalization, and use a modular structure and combine the current equalization algorithm to give a design scheme for a series battery pack equalization system.